Psychological Trauma and the Simulated Self. (June 2014) - Silcox, Mark
In the 1980s, there was a significant upsurge in diagnoses of Dissociative Identity Disorder. Ian Hacking suggests that the roots of this tendency lie in the excessive willingness of psychologists past and present to engage in the "psychologization of trauma." I argue that Hacking makes some philosophically problematic assumptions about the putative threat to human autonomy that is posed by the increasing availability, attractiveness, and plausibility of various forms of simulated experience . I also suggest how a different set of axiological and historical assumptions might have led to a less dismissive and possibly more plausible account of this diagnostic trend.